WEIGHT LOSS FOR CHILDREN AND ADULTS WITH OBESITY AND ASTHMA: SYSTEMATIC REVIEW - Pany A.A, Muhammad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Asthma, a widespread respiratory condition affecting 339 million people globally, is closely associated with obesity, which is on the rise worldwide. This review examines the impact of weight loss on asthma in individuals dealing with obesity, drawing from randomized controlled trials in both children and adults. Method: This study followed the 2020 PRISMA guidelines to ensure research alignment with necessary standards for accuracy. Articles were retrieved from databases including PubMed database in October 2023.  Result: The search strategy produced a total of 14 results. Upon reviewing the titles and abstracts, we identified 8 papers that met the criteria for inclusion. Initially, 8 articles were excluded from consideration as they were written in a review format. After a thorough evaluation of the full-text papers, we ultimately included five papers in the final analysis, consisting of prospective analysis, cross-sectional study, retrospective analysis, experimental study, and secondary analysis to a randomized control trial.  Conclusion: Diet significantly impacts respiratory health in non-overweight/non-obese children, while obesity is linked to severe asthma exacerbations, emphasizing the need for further research and public health campaigns. Short-term dietary interventions in obese asthmatic children successfully reduce calorie intake and sugar consumption, but improvements in other dietary aspects may take time, and physical activity plays a crucial role in weight loss, especially in those with lower baseline lung function. Adding exercise to weight loss interventions in obese adults with asthma yields multiple benefits, including reduced depression symptoms and improved asthma control, and moderate weight loss can delay dynamic hyperinflation, enhancing quality of life and clinical control, underscoring the significance of lifestyle interventions in managing asthma across different age groups.